Peningkatan Hasil Belajar Tematik Menggunakan Model Kooperatif STAD Peserta Didik Kelas 1 SD - Annisa Cynthia Yanmi; Wasitohadi Wasitohadi (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
This study aims to describe the steps of cooperative learning model application type STAD that is able to increase thematic learning outcomes the student in one of elementary schools in Salatiga. This instruments use in this study are observations sheet of teacher activities, student activities, students test outcomes and the document of learning activities. The students thematic learning outcomes in cycle 1 has only 9 students (43%) are completed from 21 students. Meanwhile in cycle 2, the writer gets the percentage ret 85% from the observer tho has observed the meeting twice. The thematic student learning outcomes in cycle 2 has 19 students who can complete the lesson (90%). It means that the thematic learning process with cooperative learning type STAD can run well. By studying the result, the writer can conclude that the implementation the steps of cooparative learning type STAD can increase the thematic outcomes one of elementary schools in Salatiga.